Hook Students with the Super Bowl and a Protein Modeling Activity to Teach Genetic Concepts - Ann H. Williams (American Society for Microbiology, 2014)
Teaching Biology concepts such as molecular genetics and inheritance patterns to students in K-12 and college is challenging. The created Super Bowl Activity uses kinesthetic and visual models and a "hook" to engage students in the material. Through guided inquiry and modeling, this lesson reviews concepts of DNA, mutations, genotype/phenotype, transcription, translation, homozygous/heterozygous, and inheritance patterns while entertaining the students with a story of a football player with sickle cell trait who couldn’t play in the Super Bowl. The students create a mutated and normal folded hemoglobin protein model based on amino acid chemical character and use them to simulate Mendelian genetics, inheritance patters, and heterozygous advantage. This lesson can be used by teachers and professors teaching middle/high school Biology courses as well as Undergraduate Introductory and non-major Biology courses. This teaching model was created to address content areas where students perform poorly on standardized Biology exams and was presented at a series of professional development workshops for secondary and undergraduate Biology teachers. One Biology instructor utilized it successfully in her Biology course as a review for end of course exams and felt the students were very engaged in the activity and material.